The investigation of tobacco smoke influence on the changes of indoor radon and its short-lived decay products volumetric activities - Jasaitis, Dainius; Girgždys, Aloyzas (Journal of Environmental Engineering and Landscape Management, 2013)
The changes of radon and its short-lived decay products were investigated in accommodations under natural living conditions and in tobacco smoke-filled premises. The measured radon and its short-lived decay products volumetric activities, aerosol particle concentration in the air, radioactive equilibrium factor, unattached fraction factor values are presented. It was identified that the increase of aerosol particles concentration in the air (in smoke-filled premises) determines the increase of the unattached nuclides of radon short-lived decay products attached to aerosol particles (the average values of radioactive equilibrium factor varied from 0.35 to 0.72). In this case, larger volumetric activity of the alpha particles is registered. Therefore larger amount of radon progeny is inhaled in smoke-filled premises and there is an increased possibility of damaging the organism. Positive correlation (r = 0.9) between the radioactive equilibrium factor and aerosol particle concentration in the air of accommodation, as well as negative correlation (r = −0.64) between the radioactive equilibrium factor and unattached fraction factor have been determined. Seasonal changes of the radioactive equilibrium factor are presented.